Protein microcrystallography using synchrotron radiation. (2017) - Yamamoto, Masaki; Hirata, Kunio; Yamashita, Keitaro; Hasegawa, Kazuya; Ueno, Go; Agoa, Hideo; Kumasaka, Takashi
No abstract available